2017
DOI: 10.1007/s00228-017-2318-z
|View full text |Cite
|
Sign up to set email alerts
|

SLCO1B1 521T > C polymorphism associated with rosuvastatin-induced myotoxicity in Chinese coronary artery disease patients: a nested case–control study

Abstract: SLCO1B1 (rs4149056, 521T > C) is associated with statin-induced myotoxicity in Chinese patients with coronary artery disease. In addition, SLCO1B1 521C mutant allele increased the risk of rosuvastatin-associated myotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 32 publications
1
36
0
1
Order By: Relevance
“…The mutation allele frequency of SLCO1B1 388A>G was 74.99% (74.57% in male and 75.69% in female), and 521T>C was 11.50% (12.38% in male and 10.04% in female) in the Hakka population in our research. The results were similar to the study results of Liu et al, the allele frequency of SLCO1B1 388A>G was higher in Chinese Han than in Caucasians, while 521T>C was lower. The frequencies of haplotypes *1b/*1b (40.07%) and *1a/*1b (32.56%) of SLCO1B1 gene accounted for 72.63%, followed by *1b/*15 (14.40%), *1a/*1a (5.82%), *1a/*15 (5.57%), *15/*15 (1.45%), and *1a/*5 (0.12%).…”
Section: Discussionsupporting
confidence: 91%
“…The mutation allele frequency of SLCO1B1 388A>G was 74.99% (74.57% in male and 75.69% in female), and 521T>C was 11.50% (12.38% in male and 10.04% in female) in the Hakka population in our research. The results were similar to the study results of Liu et al, the allele frequency of SLCO1B1 388A>G was higher in Chinese Han than in Caucasians, while 521T>C was lower. The frequencies of haplotypes *1b/*1b (40.07%) and *1a/*1b (32.56%) of SLCO1B1 gene accounted for 72.63%, followed by *1b/*15 (14.40%), *1a/*1a (5.82%), *1a/*15 (5.57%), *15/*15 (1.45%), and *1a/*5 (0.12%).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, a recent whole-exome sequencing endeavour reported that SLCO1B1 rs4149056 is associated with statin myopathy (mainly SVT or CVT cases), which reached multiple testing significance when limited to patients not on a fibrate; however, no novel rare coding signals were detected [111]. Intriguingly, SLCO1B1 rs4149056 has been recently associated with RVT myotoxicity (a composite of myalgias to rhabdomyolysis) in Han Chinese patients [109,176], although it was not previously associated with myalgias in patients of European descent receiving RVT [112]. A recent meta-analysis, largely including these studies, further suggested an association between rs4149056 and RVT myotoxicity [116].…”
Section: Slco1b1 Influx Transportermentioning
confidence: 99%
“…However, the situation is more complex than that and sex and ethnicity are also relevant. Thus, the same SLCO1B1 polymorphism has recently been shown to be associated with increased myotoxicity in Chinese people receiving rosuvastatin 19. There is as yet no evidence to support the cost effectiveness of screening for this polymorphism or for those in other genes, before starting statins.…”
Section: Statin-related Myopathiesmentioning
confidence: 99%